Swift loss of coherence of soliton trains in attractive Bose-Einstein condensates - Streltsov, Alexej Iwanowitsch; Alon, Ofir E.; Cederbaum, Lorenz S. (Physical review letters, 2011)
Experiments on ultracold attractive Bose-Einstein condensates (BECs) have demonstrated that at low dimensions atomic clouds can form localized objects, propagating for long times without significant changes in their shapes and attributed to bright matter-wave solitons, which are coherent objects. We consider the dynamics of bright soliton trains from the perspective of many-boson physics. The fate of matter-wave soliton trains is actually to quickly lose their coherence and become macroscopically fragmented BECs. The death of the coherent matter-wave soliton trains gives birth to fragmented objects, whose quantum properties and experimental signatures differ substantially from what is currently assumed.
Gesehen am 24.10.2022